1986
DOI: 10.1002/cne.902490108
|View full text |Cite
|
Sign up to set email alerts
|

Three morphologically distinct types of interface develop between adult host and fetal brain transplants: Implications for scar formation in the adult central nervous system

Abstract: The development of the host/graft interface of cerebellar and cerebral transplants was studied 1-60 days after operation. Grafts from fetal Wistar rats were transplanted to a cavity over the superior colliculus of adult rats by removing parts of the overlying cortex and hippocampus according to the Björklund/Stenevi technique. In sham-operated control rats, in which a cavity was made in the brain but no graft was implanted, the parenchyma bordering the entire cavity developed a complete glial-meningeal scar wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(39 citation statements)
references
References 40 publications
1
37
0
1
Order By: Relevance
“…The advantage of initially fluid transplants over pregelled ones may be i) in pregelled SC bridges, components in Matrigel, such as collagen type IV and laminin, may self-assemble into basal lamina (73) before transplantation and thereby contribute to a mesh-work of astrocyte processes similar to the glial limitans (23,24,40), and ii) fluid mixtures may rapidly conform to the surface of the cord stumps, thereby limiting the invasion of meningeal fibroblasts and inflammatory cells, analogous to duraplasty (30,31,82). The invasion of meningeal cells and their interaction with astrocytes creates glial limitans-like structures that may impede axonal growth (33,39,65). …”
Section: Discussionmentioning
confidence: 99%
“…The advantage of initially fluid transplants over pregelled ones may be i) in pregelled SC bridges, components in Matrigel, such as collagen type IV and laminin, may self-assemble into basal lamina (73) before transplantation and thereby contribute to a mesh-work of astrocyte processes similar to the glial limitans (23,24,40), and ii) fluid mixtures may rapidly conform to the surface of the cord stumps, thereby limiting the invasion of meningeal fibroblasts and inflammatory cells, analogous to duraplasty (30,31,82). The invasion of meningeal cells and their interaction with astrocytes creates glial limitans-like structures that may impede axonal growth (33,39,65). …”
Section: Discussionmentioning
confidence: 99%
“…If intermediate glial filaments could be transiently removed, then perhaps transplantation outcomes might be greatly improved (Quinlan and Nilsson, 2004). However, earlier studies (Kruger et al, 1986) have shown that scar formation can be suppressed to some extent by embryonic cell grafts and it is possible that this property may be shared by HESCs (Zhang et al, 2007).…”
Section: Mü Ller Cells and Gliosismentioning
confidence: 95%
“…1A, 3A,B) (Stichel and Müller 1994b;Blaugrund et al 1993;Richardson et al 1982;Schnell and Schwab 1993). Only single axons either emit short sprouts into the scar, where they end locally (FrisØn et al 1993;Li and Raisman 1995), or they are deflected and bypass the lesion scar via bridges of connective tissue, blood vessels or surviving tissue (Clemente 1955;Guth et al 1983;Krüger et al 1986).…”
Section: Scarring and Regeneration Failurementioning
confidence: 96%